Insufficient Higher Order Thinking Skill in Reading Comprehension Exercises of an English Language Textbook - Dewayani, Gracia Putri; Ngadiso, Ngadiso; Sarosa, Teguh (ELT Worldwide: Journal of English Language Teaching, 2020)
Higher order thinking skill (HOTS) is an important outcome standard of higher education in any discipline. Accordingly, English language textbook should present higher order thinking questions to promote students’ higher order thinking skill. The aim of this research is to analyze the extent to which the higher order thinking skill (HOTS) and the indicators of reading skill are assessed in the reading comprehension exercises. This research used the descriptive analytical method of research, which refers to content analysis. The data are analyzed based on revised Bloom’s taxonomy and reading skill indicators. The findings reveal that: (1) HOTS in the reading comprehension exercises questions only includes analyzing skill and evaluating skill while creating skill is not found; and (2) the indicators of reading skill are not fully assessed from the questions in the reading comprehension exercises in English language textbook for twelfth grade students by Indonesian Ministry of Education and Culture. The textbook only assesses topic, explicit meaning, and implicit meaning indicators. Students will not achieve higher order thinking skill and reading skill excellently if they only practice reading comprehension exercises from the textbook.